A Two‐Photon Dye with Favorable Photophysical Properties and Ultrahigh Polarity Sensitivity Designed by Utilizing the Tautomerism of β‐Diketone. Issue 2 (15th November 2016) - Li, Yu; Zeng, Lingyu; Zhong, Cheng; Dong, Xiaohu; Mao, Zhiqiang; Liu, Zhihong; Lv, Songwei; Zhang, Zhengguo; Qin, Jingui
Abstract : The designed two‐photon dye with a β‐diketone moiety can undergo a keto‐enol equilibrium and thus impart ultrahigh polarity sensitivity. The enol form, as the main component in aprotic environments with a long conjugated chain, displays much stronger two‐photon fluorescence, while the keto form in protic environments with negligible fluorescence shows good water‐solubility and cell membrane permeability.